In Memoriam – Professor Erwin Stein - Kuczma, Mieczysław (Computer Assisted Methods in Engineering and Science, 2019)
Erwin Stein nationally and internationally highly renowned scholar with outstanding achievements and important contributions to the development of computational mechanics passed away on 19th December 2018 at the age of 87. He was a mentor and a dear friend to many of us in the community of computational mechanics.